An Improved Enzyme-Linked Focus Formation Assay Revealed Baloxavir Acid as a Potential Antiviral Therapeutic Against Hantavirus Infection - Ye, Chuantao; Wang, Dan; Liu, He; Ma, Hongwei; Dong, Yangchao; Yao, Min; Wang, Yuan; Zhang, Hui; Zhang, Liang; Cheng, Linfeng; Xu, Zhikai; Lei, Yingfeng; et al. (Frontiers in Pharmacology, 2019)
Hantaviruses, etiologic pathogens responsible for two severe human diseases, exist in areas ranging from Eurasia to America and remain global public health concerns. Conventionally, plaque formation assays have been used for hantavirus titering. However, hantaviruses replicate slowly within cells and produce minimal cytopathic effects, making this technique difficult to master. The improved enzyme-linked immunosorbent assay-based antigen detection method is easier to perform but is still time consuming. Here, we established an enzyme-linked focus formation assay (FFA) for Hantaan virus titering that is twice as fast as traditional assays. Moreover, using this method, we evaluated the effects of favipiravir (T-705) and another influenza virus drug, baloxavir acid (BXA), on hantavirus replication. We found that the endonuclease inhibitor BXA exerted similar anti-hantavirus effects as T-705. Overall, we developed a time-saving method for hantavirus titering and suggest BXA as a potential treatment choice for hantavirus-exposed individuals.